RESHAPING NORTH MACEDONIA: THE NAME CHANGE AND THE PRESPA AGREEMENT (Security Dialogues, 2025)
The Balkans have been a significant region in political history. Despite being asmall, mountainous country without a coastline, Macedonia’s territory has been a significantregion throughout history, attracting the attention of major powers due to its strategiclocation. Following the breakup of Yugoslavia in 1991, Macedonia declared its independence.During this period, Greece reacted strongly against the independence. In this context, NorthMacedonia has been experiencing a name and other crisis. According to Greece, Macedoniadoesn’t have the territory to use this name, flag, and the national anthem. In addition, theyblame to Macedonia with appropriate to Greek cultural values as, Vergina Sun, Alexanderthe Great. Also, the statue of Alexander the Great built in the center of Skopje, renamingof Skopje airport to “Alexander the Great Airport,” and the description of the ThessalonikiTower on the Macedonian currency have all been perceived as provocative actions by Greece.Greece identifies Macedonia’s historical and cultural heritage with its own identity, whilethe presence of minorities also raises concerns. Additionally, the fact that the preambleof the “Constitution of the Republic of Macedonia” states that the principles of the 1944ASNOM Declaration are inherited and emphasizes that Macedonians living in the territoriesof Greece and Bulgaria will be united under the Macedonian Socialist Republic, constitutesone of the main reasons for Greece’s concerns. Greece has clearly opposed the use of thename “Macedonia” by rejecting both the existence of the Macedonian minority living withinits borders and the recognition of the Macedonian nation. Greece has created internationalpressure for the resolution of the name issue by blocking Macedonia’s NATO and EuropeanUnion membership process. After the discussions, the Prespa Agreement was signed in 2018(Gounaris & Kofos, 2019).
Keywords: Macedonia, Greece, Name dispute, Cultural heritage, Identity